2020
DOI: 10.1101/2020.09.04.283853
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-clinical studies of a recombinant adenoviral mucosal vaccine to prevent SARS-CoV-2 infection

Abstract: There is an urgent need to develop efficacious vaccines against SARS-CoV-2 that also address the issues of deployment, equitable access, and vaccine acceptance. Ideally, the vaccine would prevent virus infection and transmission as well as preventing COVID-19 disease. We previously developed an oral adenovirus-based vaccine technology that induces both mucosal and systemic immunity in humans. Here we investigate the immunogenicity of a range of candidate adenovirus-based vaccines, expressing full or partial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Additionally, it was concluded that stabilizing the spike protein in its pre-fusion conformation is not necessary in nucleic acid vaccines, since it does not induce higher neutralizing antibody (NAb) titers in murine models compared to the non-stabilized version. Nevertheless, this has not been reported in other Ad vaccines 99,100 .…”
Section: Adenoviral Vector Vaccines For Sars-cov-2mentioning
confidence: 67%
“…Additionally, it was concluded that stabilizing the spike protein in its pre-fusion conformation is not necessary in nucleic acid vaccines, since it does not induce higher neutralizing antibody (NAb) titers in murine models compared to the non-stabilized version. Nevertheless, this has not been reported in other Ad vaccines 99,100 .…”
Section: Adenoviral Vector Vaccines For Sars-cov-2mentioning
confidence: 67%
“…Access to vaccines heavily depends on their formulations which are often delicate and require storage in coolers or cryotanks, presenting challenges in transportation and cold-chain distribution [ 243 ]. An oral adenovirus based-vaccine for SARS-CoV-2 S protein has been developed in response to these challenges, offering advantages of utilizing mucosal immunity with ease of storage and needle-free applications [ 244 ].…”
Section: Covid-19 Vaccinesmentioning
confidence: 99%
“…The company Vaxart has developed a vaccine that uses a nrVV adenovirus type-5 (Ad5), that encodes the complete S glycoprotein as it is expressed by the original SARS-CoV-2, preserving all the components of the S1 and S2 subunits ( 64 ). Similarly, the company Arcturus Therapeutics has used a complete S glycoprotein without modifications, however, they have opted for technologies of a self-replicating mRNA ready for translation ( 65 ).…”
Section: S Glycoprotein In Sars-cov-2 Vaccinesmentioning
confidence: 99%